Problematika Pembelajaran Sejarah di SMAN 2 Rambatan Pada Masa Pandemi Covid-19 - Rezi Delila Arjun; Wahidul Basri (Jurusan Sejarah FIS UNP, 2021)
he purpose of this study is to explain the problem of the combined online offline learning system in history subject in class XI social in SMA Negeri 2 Rambatan, it is interesting to study because SMA Negeri 2 Rambatan is one of the schoo in West Sumatera carrying out a combined online and offline laerning system during the Covid-19 pandemic, in this implementation according to the circular letter of the regent Tanah Datar, but in implementing the online and offline combination learning system on histor class XI social subject in SMA Negeri 2 Rambatan during the Covid-19 pandemicexperienced obtacles in the implementation of the learning. this research uses a qualitative approach, the selection of informants is carried out by purposive with twentyfive informants, collecting data by observation, indepth interview and documentation studies.The result of the research that did while in the field were the problems of the online/offline combination learning system that were felt by tudent 1. Student has difficulity adjusting to combination learning, 2. Limited facilities and infrastructure, 3. Teachers do not prepare innovative methods, media and learning resources. 4. Lack of student motivation in learning, 5. Low student learning outcomes, 6. Student cannot afford internet packages, 7. Student difficulties in accesing the internet network. As for the problems with the online/offline combination learning system that is felt by teacher. 1. The teacher does not have the skill/knowledge, 2. Teacher have difficulty in providing an assesment of combined learning. 3. Ineffective teaching time for student. 4. The ability of history teacher to use information technology is limited. 5. Limited facilities an infrastructure.